2021
DOI: 10.3390/life12010016
|View full text |Cite
|
Sign up to set email alerts
|

Ibogaine Has Sex-Specific Plasma Bioavailability, Histopathological and Redox/Antioxidant Effects in Rat Liver and Kidneys: A Study on Females

Abstract: Ibogaine induces rapid changes in cellular energetics followed by the elevation of antioxidant activities. As shown earlier in male rats, ibogaine treatment with both 1 and 20 mg/kg b.w. per os led to significant glycogenolytic activity in the liver. In this work, female rats treated with the same doses of ibogaine per os displayed lower liver glycogenolytic activity relative to males, dilatation of the central vein and branches of the portal vein, and increased concentration of thiols 6 h after treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In the case of ibogaine, preclinical studies have shown sex-specific effects in rodents. For example, after ibogaine's administration, females showed higher plasma bioavailability and concentration in the brain than male rodents [33,34]. Yet, to our knowledge, there are no previous preclinical reports studying sex differences following noribogaine administration.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of ibogaine, preclinical studies have shown sex-specific effects in rodents. For example, after ibogaine's administration, females showed higher plasma bioavailability and concentration in the brain than male rodents [33,34]. Yet, to our knowledge, there are no previous preclinical reports studying sex differences following noribogaine administration.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, female sex is among the additional risk factors for drug-induced TdP arrhythmias that should be considered before the use of ibogaine [ 6 ]. Previous results have shown that the bioavailability of ibogaine and its principal in vivo metabolite, noribogaine, is two to three times higher in female rats than in male rats [ 9 , 10 ] and that ibogaine has sex-specific effects on the central nervous system [ 11 , 12 , 13 ], liver, and kidneys, with ibogaine-induced pathological changes being more pronounced in female rats [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in several in vitro, ex vivo and in vivo experimental models that the biological activity of ibogaine, in addition to involving interaction with various types of receptors [ 2 , 16 , 17 ], is caused by rapid depletion of ATP, which is followed by an induction of enzymes related to energy metabolism, as well as increases in cellular reactive oxygen species (ROS) and the activity of antioxidant enzymes [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In our previous experiments in rats treated per os it was shown that ibogaine affected energy metabolism, antioxidant defense, and redox balance without life-threatening pathological effects on the liver and kidneys [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations